A highly efficient polymer non-fullerene organic solar cell enhanced by introducing a small molecule as a crystallizing-agent. Issue 1 (January 2018) - Zheng, Yifan; Huang, Jiang; Wang, Gang; Kong, Jaemin; Huang, Di; Mohadjer Beromi, Megan; Hazari, Nilay; Taylor, André D.; Yu, Junsheng
Graphical abstract: Such devices allow precise morphology control of the active layer, while realizing the highly efficient exciton dissociation. Overall, by fully understanding the mechanism of crystallizing-agent, we obtain a power conversion efficiency enhancement from 8.98% to 10.86%. Abstract: Non-fullerene organic solar cells (OSCs) have attracted tremendous interest because of their potential to replace traditional expensive fullerene-based OSCs. To further increase the power conversion efficiency (PCE), it is necessary to offset the narrow absorption of the non-fullerene materials, which is often achieved by adding an additive (>10 wt%) to form a ternary blend. However, a high ratio of the third component can often be detrimental to the active layer morphology and can increase the complexity in understanding the device physics toward rationally designed improvements. In this work, we introduce 2, 4-bis-[(N, N-diisobutylamino)-2, 6-dihydroxyphenyl]-4-(4-diphenyliminio) squaraine (ASSQ) in the poly [(2, 6-(4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl) benzo [1, 2-b:4, 5-b′] dithiophene)-co-(1, 3-di(5-thiophene-2-yl)-5, 7-bis(2-ethylhexyl) benzo [1, 2-c:4, 5-c′] dithiophene-4, 8-dione)] (PBDB-T): 3, 9-bis(2-methylene-(3-(1, 1-dicyanomethylene)-indanone))-5, 5, 11, 11-tetrakis(4-hexylphenyl)-dithieno [2, 3-d:2′, 3′-d′]-s-indaceno [1, 2-b:5, 6-b′] dithiophene (ITIC) as an active layer "crystallizing-agent". Through detailed morphology characterization, we find that the addition of 4 wt% ASSQ assists ITIC organization order and promotes PDBD-T:ITIC aggregation in the preferential face-on orientation. In addition, we demonstrate that the ASSQ and PBDB-T show efficient exciton dissociation in the ternary blend over Förster resonance energy transfer (FRET). We reveal using surface potential and solubility measurements that a ASSQ-ITIC co-crystalline structure forms which facilitates a significant improvement in the device PCE, from 8.98% to 10.86%.